On the concept of territorial competitiveness: sound or misleading? - Roberto Camagni (European Regional Science Association (ERSA), 2002)
In a globalising economy, territories and not just firms increasingly find themselves in competition with each other. In fact, differently from the case of countries, cities and regions compete, on the international market for goods and production factors, on the basis of an absolute advantage principle, and not of a comparative advantage principle; this means that no efficient, automatic mechanism like currency devaluation or prompt flexibility of wages and prices - may grant each territory some role in the inter-national division of labour, whatever its relative performance. Competitiveness of territories emerges as a central issue, in order to secure employment stability, benefits from external integration, continuing growth of local wellbeing and wealth. The arguments put forward by Paul Krugman, defining the concept of competitiveness wrong and misleading, cannot be accepted in a territorial 'regional and urban' context.
Keywords: 330